Prinsip-Prinsip Etika Profesi Hukum dan Bisnis Syariah - Kharisma Febri Yanti; Helma Rohimah; Putri Fitria Nurwati; Putri Purnama Sari; Surya Sukti (STIKes Ibnu Sina Ajibarang, 2025)
This article discusses the importance of professional ethics in the legal profession. The legal profession is a vital component of modern society, and its practitioners play a crucial role in upholding justice and promoting the rule of law. However, the legal profession is not immune to ethical challenges, and its practitioners must adhere to a strict code of ethics to maintain public trust and confidence. This paper examines the fundamental principles of professional ethics in the legal profession, including confidentiality, competence, and integrity. It also discusses the consequences of unethical behavior and the importance of promoting an ethical culture within the legal profession.